THE RELATIONSHIP BETWEEN SELECTED MARKET ORIENTATION DIMENSIONS AND ORGANIZATIONAL PERFORMANCE WITHIN UNIVERSITIES IN SOUTH AFRICA - MOKOENA, Bakae Aubrey (Studia Universitatis Babeș-Bolyai Oeconomica, 2019)
The association of market orientation and organisation performance has been the focal point of several studies that confirmed a positive relationship between the constructs. However, there is a lack of evidence in studies examining this issue within universities of technology (UoTs) in South Africa. Hence, the study was undertaken with the main objective of conducting an analysis on the dimensions of MARKOR scale of market orientation in the prediction of university performance within UoTs in South Africa. Both the resource based view theory and the dynamic capacity theory were identified as the foundation of the study. Considering the situational factors and the institutions’ environment, a non-probability sampling procedure was chosen. A convenience sample of 507 full-time employed academics within the six UoTs in South Africa, participated in a cross-sectional survey through a self-administered structured questionnaire. The factor analysis procedure resulted in the extraction of three primary dimensions, namely market information generation, market information dissemination and responsiveness. A conceptual research model was tested using confirmatory factor analysis. Through multiple regression analysis, the results show that market information generation, market information dissemination and responsiveness are significant predictors of university performance. The findings contribute to an enhanced comprehension of the dimensions of MARKOR scale towards predicting university performance among UoTs in South Africa. The study provides possible recommendations and extends immensely the existing knowledge among researched concepts when measuring organisational performance. JEL Classification: M30, M31, M39, M12, M54